Gezira j. of agric. sci. 15 (1): 13-25 (2017) Physico-chemical changes during growth and development of grapefruits (Citrus paradisi Macf.). IІ. Chemical changes - Abu-Goukh, Abu-Bakr Ali; Mohammed Almahi, Ali Azhari (Gezira Journal of Agricultural Science; Vol 15 No 1 (2017), 2017)
The chemical changes during growth and development of seedy pink-fleshed ‘Red Blush’ grapefruits were evaluated to provide base-line information regarding the biochemistry of the developing fruit and to assist in determining harvest maturity of grapefruits. The fruits exhibited a typical non-climacteric pattern of respiration. Respiration rate decreased from 239.8 mg CO 2 /kg-hr (4 WAA) to 21.1 mg CO 2 /kg-hr (26 WAA). Total soluble solids (TSS) and total sugars progressively increased from 4 weeks after anthesis (WAA) up to 26 WAA at physiological maturity, and then remained constant. Reducing sugars, titratable acidity and ascorbic acid content progressively increased from 4 WAA, reaching a peak at 16, 10 and 8 WAA, respectively, and then declined to minimum values at physiological maturity.  Grapefruits should be harvested at least at physiological maturity, where the fruit attains maximum size and weight, rind color develops, TSS and total sugars reach above 14% and 14 g/100g fresh weight, titratable acidity is reasonably low, ascorbic acid content reasonably high and the fruit is still firm.                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                  قومت التغيرات الفيزيائية أثناء النمو والتطور لثمار القريب فروت أحمر اللب ذي البذور من الصنف "رد بلش"، وذلك لتوفير المعلومات الأساسية المتعلقة بكيمياء الثمار أثناء تطورها لتساعد في تحديد مرحلة اكتمال النمو لثمار القريب فروت. تبع معدل تنفس الثمار نمط التنفس غير الكلايماكتيرى، حيث انخفض من 239.8  ملجم ثاني أكسيد الكربون/ كجم- ساعة (4 أسابيع بعد تفتح الأزهار) إلى 21.1 ملجم ثاني أوكسيد الكربون/ كجم- ساعة (26 اسبوعاٌ بعد تفتح الأزهار). زادت نسبة المواد الصلبة الكلية الذائبة والسكريات الكلية زيادة مطردة في الثمار من 4 أسابيع بعد تفتح الأزهار إلى 26 اسبوعاٌ بعد تفتح الأزهار، عند مرحلة اكتمال النمو الفسيولوجي، ثم ثبتت على ذلك فيما بعد. زادت السكريات المختزلة والحموضة القابلة للتعادل وحامض الأسكوربيك زيادة مطردة بعد 4 أسابيع من تفتح الأزهار حتى وصلت إلى قمة بعد 16 و10 و8 أسابيع بعد تفتح الأزهار، على التوالي، ثم انخفضت بعد ذلك إلى أدنى مستوياتها عند مرحلة اكتمال النمو الفسيولوجي. لذلك يجب حصاد ثمار القريب فروت عند مرحلة اكتمال النمو الفسيولوجي، على الأقل، حيث تكون الثمرة قد بلغت الحجم والوزن النهائي، والقشرة قد تلونت، وبلغت نسبة المواد الصلبة الكلية الذائبة فيها أكثر من 14 %، والسكريات الكلية أكثر من 14 جرام/ 100 جرام، والحموضة المعايرة منخفضة نسبياً، وحامض الأسكوربيك مرتفع بالقدر المناسب، وتكون الثمرة ما زالت صلبة القوام.